Psicologia e tecnologia: a formação profissional em psicologia - Braga, Daiane Suelen da Silva (2023)
Scientific, theoretical and practical rigor confers an integral character on the individual's formative process and must be associated, conferring critical and acting capacity, since the appropriation of culture by the subject would not, in this case, be replaced by the appropriation of the subject by the capital in a reproductive and fragmented way. This research has as its main objective the analysis of training and, specifically, training in psychology, as well as its movement resulting from industrialization supported by expressive technological development. Through this understanding, this research, arising from a documental analysis of the 2004 national curriculum guidelines (DCNs, 2004) for the formation of courses in psychology and the pedagogical projects of the University of Taubaté, from 2004 and 2016, sought to compare the data over the years. historical transitions of delimitation of the psychologist's training field, in order to elucidate the concept of the so-called generalist training. Through the analysis of the 2004 National Curriculum Guidelines, carried out in the procedures and elucidated in the discussion of this study, as well as by its materialization under the elaboration of the curricula of the University of Taubaté, an effort was identified to guide the course emphasizing practical action, supported by the notion of competencies and skills, but also a gap is identified regarding the possibility that a course with its own characteristics and permeated by a certain autonomy fails to develop given the non-discussion of these guidelines. From the perspective of the Critical Theory of Society, it identified through the analysis of the information obtained that the National Curriculum Guidelines (2004/2011) are guidelines regarding the structure that the courses follow, but they are responsible for a critical appropriation of their content and, as described in the results of this study, resolutions distanced from debate and criticism corroborate to accelerate and produce pseudotraining, insofar as they become just instruments and operate as a reproduction mode for the individual's adaptation